HOME MEDICINE REVIEW ELDERLY BASED ASSESSMENT OF MEDICATION RELATED PROBLEMS IN MYSURU CITY - KUMAR, JAIDEV; MAHENDRAPPA (International Journal of Current Pharmaceutical Research, 2019)
Objective: To assess the medication related problems among chronically ill patients. Methods: Patients who met study criteria were enrolled in this research study, followed by standard operating procedure of home medicine review was applied to carry out this research study. Drug related problems of enrolled patients were evaluated by applying Hepler and Strand drug related problem scale. Results: The pharmacist intervention rate in this research study was found 58%. The medication related problems identified in this study were drug given without indication which was accountable for 32 % followed by drug duplication 5.21%, drug interactions 11% and adverse drug reactions 6.52 %. Conclusion: This research study concludes that prevalence of drug related problems among elderly patients were accountable for 40.49 % among Home Medicine Review in Mysore city due to more comorbidity which had resulted more number of medications with respect to individual medical case. Elderly patients will have lot of confusion which makes difficult to follow strict directions of medications prescribed by concerned consultant.